2014
DOI: 10.3390/toxics2010050
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry and Toxicology of Depleted Uranium

Abstract: Natural uranium is comprised of three radioactive isotopes: 238 U, 235 U, and 234 U. Depleted uranium (DU) is a byproduct of the processes for the enrichment of the naturally occurring 235 U isotope. The world wide stock pile contains some 1½ million tons of depleted uranium. Some of it has been used to dilute weapons grade uranium (~90% 235 U) down to reactor grade uranium (~5% 235 U), and some of it has been used for heavy tank armor and for the fabrication of armor-piercing bullets and missiles. Such weapon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 83 publications
0
25
0
Order By: Relevance
“…The cause behind such results can be attributed to the high levels of uranium contamination in the region of southern Iraq as a result of military activities during the Gulf Wars which led to the exposure of individuals to high levels of radioactive pollution [1,2]. From Table 2, it was found that observed uranium concentrations in kidney were widely scattered and the average uranium concentration (6.51 lg kg -1 ) for abnormal tissues and (4.11 lg kg -1 ) for normal tissues was higher than those in the other abnormal and normal soft tissues, because the kidney is one of the principle sites of uranium deposition in the body [34]. This finding is in agreement with those of other researchers [32,35].…”
Section: Resultsmentioning
confidence: 99%
“…The cause behind such results can be attributed to the high levels of uranium contamination in the region of southern Iraq as a result of military activities during the Gulf Wars which led to the exposure of individuals to high levels of radioactive pollution [1,2]. From Table 2, it was found that observed uranium concentrations in kidney were widely scattered and the average uranium concentration (6.51 lg kg -1 ) for abnormal tissues and (4.11 lg kg -1 ) for normal tissues was higher than those in the other abnormal and normal soft tissues, because the kidney is one of the principle sites of uranium deposition in the body [34]. This finding is in agreement with those of other researchers [32,35].…”
Section: Resultsmentioning
confidence: 99%
“…Most commonly, inorganic soluble uranium salts are uranyl nitrate, uranyl fluoride, uranium tetrachloride, uranyl acetate, and sulphate. Uranium dissolves readily in hydrochloric acid and nitric acid but slowly in sulphuric acid (Katz, ). Combustion of fossil fuels may result in formation of NOx and SOx gases, which dissolve in rain drops and form nitric and sulphuric acid.…”
Section: Can Uranium and Nitrate Compounds Act As Facilitators Of Ckd?mentioning
confidence: 99%
“…In general, it appears that imbedded DU is not a reproductive or developmental hazard. However, the elevated heart masses of the first-and second-generation offspring suggest it may be precautionary to not totally discount the possibility of teratogenic effects [48,49]. The results of another study suggest that implantation of up to 20 DU pellets of 1 × 2 mm size in rats for approximately 21% of their adult lifespan does not have an adverse impact on male reproductive success, sperm concentration, or sperm velocity [50] and on their general health and neurobehavioral capacities [51].…”
Section: Chemical Toxicitymentioning
confidence: 99%